2023
DOI: 10.1186/s12903-023-02933-z
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the COVID-19 pandemic, sex, and age on temporomandibular disorders subtypes in East Asian patients: a retrospective observational study

Abstract: Background Despite its major existential, societal, and health impacts, research concerning the COVID-19 pandemic and Temporomandibular disorders (TMDs) is still limited. This study examined the effect of the pandemic on TMD subtypes and elucidated the influence of the pandemic, sex, and age on the prospect of pain-related (PT) and/or intra-articular (IT) TMDs in East Asian patients. Methods Data were accrued from consecutive new patients attending… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…Moreover, the PT group consisted of older individuals, whilst the CT group had a more prolonged history of TMD contrasted to the other groups. The findings corroborated previous studies, demonstrating the contributory roles of sex and age in the pathophysiology of TMD [ 4 , 29 31 ]. The extended TMD duration observed in the CT group could be attributed to the time taken to develop both TMD pain and dysfunction, prompting individuals to seek treatment for their symptoms.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, the PT group consisted of older individuals, whilst the CT group had a more prolonged history of TMD contrasted to the other groups. The findings corroborated previous studies, demonstrating the contributory roles of sex and age in the pathophysiology of TMD [ 4 , 29 31 ]. The extended TMD duration observed in the CT group could be attributed to the time taken to develop both TMD pain and dysfunction, prompting individuals to seek treatment for their symptoms.…”
Section: Discussionsupporting
confidence: 91%
“…Yap et al suggested that the prevalence of pain-related and intra-articular (non-painful) TMD among East Asian patients was not significantly affected by the COVID-19 pandemic and suggested that sex and age play a more crucial role in the development of painful and non-painful TMD than the pandemic [ 56 ]. It is noteworthy that Yap et al refer to two time periods only (before and during the pandemic).…”
Section: Discussionmentioning
confidence: 99%